2003
DOI: 10.1002/pd.567
|View full text |Cite
|
Sign up to set email alerts
|

Successful early in utero management of fetal hydrothorax in a twin pregnancy

Abstract: We present a case of dichorionic diamniotic twin pregnancy in which one of the fetuses was found to have a major pleural effusion at 15 weeks of gestation. A single-needle pleural fluid aspiration was performed at 15 and 16 weeks, but the fluid reaccumulated quickly after each procedure and at 16 weeks, the fetus was found to become progressively hydropic. A shunt was then successfully inserted at 17 weeks, which is the earliest gestation reported so far in the literature for such a procedure to treat isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…1,3 Pleuroamniotic shunting has been shown effective in providing longterm intrauterine drainage after gestational week 22, 2,3,27-32 and shunting was shown to be effective in early second trimester (gestational weeks 17 and 19) in two case reports. 8,9 However, it is a technically difficult procedure because of the relatively large gauge of the instruments needed for placing the shunts, and shunt replacements are often required. Further, the position of the fetus and the placenta may prevent the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Pleuroamniotic shunting has been shown effective in providing longterm intrauterine drainage after gestational week 22, 2,3,27-32 and shunting was shown to be effective in early second trimester (gestational weeks 17 and 19) in two case reports. 8,9 However, it is a technically difficult procedure because of the relatively large gauge of the instruments needed for placing the shunts, and shunt replacements are often required. Further, the position of the fetus and the placenta may prevent the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, only two cases have described successful pleuroamniotic shunting in early second trimester. 8,9 Pleuroamniotic shunting is a technically difficult procedure, particularly at early gestational age, associated with adverse effects such as preterm labor, which is a poor prognostic factor. 1,2 Further, the position of the fetus and the placenta may prevent the procedure.…”
Section: Level Of Evidence: IImentioning
confidence: 99%
“…The natural course of pleural effusion varies from spontaneous resolution as pregnancy advances, to a progressive increase in size with subsequent mediastinal compression and deviation and fetal hydrops [9] . Longaker et al [10] reported spontaneous resolution of pleural effusion in 3 of 32 fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Serial thoracocenthesis or thoracoamniotic shunt placement improves survival. The earliest prenatal pleural drainage procedure described was performed at 17 weeks gestational age [58]. Postnatal treatment consists of thoracocenthesis, replacement of intravascular volume and protein, and prolonged parenteral nutrition or medium chain triglyceride feeding [59].…”
Section: Intrathoracic Causesmentioning
confidence: 99%